1994
DOI: 10.2337/diacare.17.7.665
|View full text |Cite
|
Sign up to set email alerts
|

Chicken and Fish Diet Reduces Glomerular Hyperfiltration in IDDM Patients

Abstract: A normoproteic diet with chicken and fish as the only meat protein source decreases the GFR in the hyperfiltering normoalbuminuric IDDM patients. The GFR reduction after this diet is similar to that observed after an LPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 29 publications
4
16
0
2
Order By: Relevance
“…In addition, several smaller studies of type 1 diabetic patients have indicated that dietary protein is not associated with the occurrence or progression of diabetic renal disease (37)(38)(39). Our findings are also in agreement with those of Pecis et al (15), who found that GFR was reduced in hyperfiltrating patients not only after a low-protein diet, but also after a switch from a red meat to a fish and chicken diet, still containing the usual amounts of protein. Thus, fish protein may decrease renal workload, thereby reducing the risk for future development of diabetic nephropathy.…”
Section: Multivariate Analysessupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, several smaller studies of type 1 diabetic patients have indicated that dietary protein is not associated with the occurrence or progression of diabetic renal disease (37)(38)(39). Our findings are also in agreement with those of Pecis et al (15), who found that GFR was reduced in hyperfiltrating patients not only after a low-protein diet, but also after a switch from a red meat to a fish and chicken diet, still containing the usual amounts of protein. Thus, fish protein may decrease renal workload, thereby reducing the risk for future development of diabetic nephropathy.…”
Section: Multivariate Analysessupporting
confidence: 93%
“…None of the patients were restricted to a low-protein diet. Although it has been shown in several studies that different protein sources may have different effects on renal function (9,14,15), not many epidemiological reports have analyzed the risk of different eating habits on the presence of microalbuminuria in young type 1 diabetic patients. The European IDDM Diabetes Complications Study Group (35) found an association between dietary protein intake and urinary AER in 2,696 patients with type 1 diabetes.…”
Section: Multivariate Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another alternative is to use a qualitative test for proteinuria (dipstick) (33) or a quantitative measurement of protein in a (60,61), and dietary factors, such as the amount and source of protein (62)(63)(64) and fat (65) in the diet.…”
Section: Stages Clinical Features and Clinicalmentioning
confidence: 99%
“…When predominantly plant protein replaced animal protein in three studies of type 1 diabetic subjects, the amount of protein consumed was also reduced significantly (653)(654)(655). Any beneficial effects may have been from reduction in the amount or change in the protein source.…”
mentioning
confidence: 99%